EFFECTS OF DIFFERENT pH SETTINGS ON GROWTH AND SURVIVAL OF COMMON CARP RAJADANU STRAIN - Vitas Atmadi Prakoso; Deni Radona (Indonesian Aquaculture Journal, 2018)
pH is one of the important water quality parameters in aquaculture. This study aimed to observe the growth performance and survival rate of common carp (Cyprinus carpio) Rajadanu strain reared in culture media with different pH levels. Fish (length: 3.60 ± 0.18 cm; weight: 1.68 ± 0.18 g) were stocked in nine aquariums (40 cm x 40 cm x 30 cm) for 10 days with a stocking density of 25 fish per aquarium. The treatments used were (A) pH 4-5, (B) pH 5-6, and (C) pH 6-7, with three replications. A commercial feed containing 28% protein was given daily and as much as 3% of the total biomass. The observed data were analyzed using variance analysis (ANOVA), followed by Duncan test. The results showed that the pH treatments did not affect the growth (length and weight) and survival rate of common carp Rajadanu strain (P>0.05). The best growth was achieved by the fish group reared in water with a pH range of 6-7 (length = 0.38 cm; weight = 0.17 g). The highest survival was attained by the fish group reared in water with a pH range of 5-6 (90.66%).